Genetic testing for hereditary prostate cancer: Current status and limitations. Issue 15 (18th April 2018) - Zhen, Jun Tu; Syed, Jamil; Nguyen, Kevin Anh; Leapman, Michael S.; Agarwal, Neeraj; Brierley, Karina; Llor, Xavier; Hofstatter, Erin; Shuch, Brian
Abstract : A significant proportion of prostate cancer diagnoses may be associated with a strong hereditary component. Men who have multiple single‐gene polymorphisms and a family history of prostate cancer have a significantly greater risk of developing prostate cancer. Numerous single‐gene alterations have been confirmed to increase the risk of prostate cancer. These include breast cancer genes 1 and 2 ( BRCA1 and BRCA2, respectively), mutL homolog 1 ( MLH1 ), mutS homologs 2 and 6 ( MSH2 and MSH6, respectively), postmeiotic segregation increased 2 ( PMS2 ), homeobox B13 ( HOXB13 ), checkpoint kinase 2 ( CHEK2 ), nibrin ( NBN ), BRCA1‐interacting protein C‐terminal helicase 1 ( BRIP1 ), and ataxia telangiectasia mutated ( ATM ). Currently, there are no uniform guidelines on the definition of hereditary prostate cancer and genetic testing. With the advent of next‐generation sequencing, which is capable of testing multiple genes simultaneously, and the approval of olaparib for BRCA1 / BRCA2 or ATM ‐mutated, metastatic, castrate‐resistant prostate cancer, it is being recognized that the results of genetic testing have an impact on therapeutic strategies. In this review, the authors examine the role of genetic counseling and testing, the challenges of insurance coverage for testing, the available germline and somatic testing panels, and the complexity of each testing method and its implications. Cancer 2018. © 2018 American Cancer Society . Abstract : A significant proportion of prostate cancer diagnoses may be associated with a strong hereditary component. Men who have multiple single‐gene polymorphisms and a family history of prostate cancer have a significantly greater risk of developing prostate cancer.